Which behavioural and exercise interventions targeting fatigue show the most promise in multiple sclerosis? A systematic review with narrative synthesis and meta-analysis. (February 2021) - Moss-Morris, Rona; Harrison, Anthony M.; Safari, Reza; Norton, Sam; van der Linden, Marietta L.; Picariello, Federica; Thomas, Sarah; White, Claire; Mercer, Tom
Abstract: Fatigue is a common and highly debilitating symptom of multiple sclerosis (MS). This meta-analytic systematic review with detailed narrative synthesis examined randomised-controlled (RCTs) and controlled trials of behavioural and exercise interventions targeting fatigue in adults with MS to assess which treatments offer the most promise in reducing fatigue severity/impact. Medline, EMBASE and PsycInfo electronic databases, amongst others, were searched through to August 2018. Thirty-four trials (12 exercise, 16 behavioural and 6 combined; n = 2, 434 participants) met inclusion criteria. Data from 31 studies (n = 1, 991 participants) contributed to the meta-analysis. Risk of bias (using the Cochrane tool) and study quality (GRADE) were assessed. The pooled (SMD) end-of-treatment effects on self-reported fatigue were: exercise interventions (n = 13) -.84 (95% CI -1.20 to -.47); behavioural interventions (n = 16) -.37 (95% CI -.53 to -.22); combined interventions (n = 5) -.16 (95% CI: -.36 to .04). Heterogeneity was high overall. Study quality was very low for exercise interventions and moderate for behavioural and combined interventions. Considering health care professional time, subgroup results suggest web-based cognitive behavioural therapy for fatigue, balance and/or multicomponent exercise interventions may be the cost-efficient therapies. These need testing in large RCTs with long-term follow-up to help define an implementable fatigue management pathway in MS. Highlights: Exercise and behavioural interventions had moderate to large effects on MS fatigue. The quality of evidence was moderate for behavioural but poor for exercise studies. There was good quality evidence of non-significant effects of energy conservation. Web-based CBT and balance interventions showed promise but require large trials. Based on limited evidence, combined interventions did not show added benefits.